Implicações clínicas, endoscópicas e eletromanométricas da escleroterapia endoscópica de varizes esofágicas em cirróticos - Coimbra, Fernando Tadeu Vannucci (2012)
Introduction and Objective: The main objective of this study is to evaluate the motor reaction of the esophagus after undergoing endoscopic sclerotherapy of esophageal varices (EE) up to its eradication. Clinical implications and the ones with endoscopic evidence were subsidiarly of interest driven by the procedure. Casuistic and Methods: Fourteen patients with liver cirrhosis with esophageal varices; nine men and five women, mean age of 52.57 ± 14.58 years, who had already had episode (s) of variceal bleeding were studied. In eleven, the disease had alcoholic origin and three viral etiology by virus type B in two, and type C in one. Twelve were classified as Child-Pugh A, and two as B. They underwent endoscopic examination before the EE, and at least, one month after the procedure, to list any complications, while also questioning on dysphagia and retrosternal pain. EE was performed with 5%- ethanolamine oleate and 50%-hypertonic glucose in equal parts. Intravasal injections of 2 to 5 ml were performed at 2 cm-intervals , starting from the esophagogastric transition, towards cranial direction in each one of the varicose cords up to the complete elimination of varicose veins, according to the limit of 20 to 30ml/varix / session, and about 15 day-interval between the sessions. Electromanometric study of esophagus was performed from two to three days before the procedure and at least one month after the end of the endoscopic treatment, before the endoscopic examination of control . The average results were compared by the Student's t test, with a 5%-significance level. Results: At initial endoscopy, varicose veins of medium caliber in 11 patients, and thick-caliber in three were observed. Red spots were found in all cases. Varicose veins were eradicated in all patients at endoscopic examination, after-procedure, carried out on average of 3.07 ± 2.97 months from the end of EE. Four sclerotherapy sessions, in the mean time of 1.6 ± 0.71 months, were necessary. There were no complications in eight cases. Four patients had superficial esophageal ulcers of ischemic aspect, in areas of sclerosis, while two others, in addition to ulcers, showed tenuous synechiae. The investigation of dysphagia and retrosternal pain showed that ten patients were asymptomatic, others maintaining evasive and low intensity symptoms. The comparison between the averages of the variables analyzed by esophageal electromanometry after EE, revealed significant reductions in resting pressure of lower esophageal sphincter (LES), percentage of LES relaxation, peristalsis percent, wave length of swallowing and extent of swallowing complexes. Conclusions: In conclusion, this procedure can completely eradicate varicose veins and, if performed moderately , does not produce important=significant tissue complications in the esophagus, or significant symptoms after finishing, but provides significant motor abnormalities of the organ, potentially capable of favoring gastroesophageal reflux and reduced ability to empty the organ.